Analysis of association between long non-coding RNA HOTAIR gene rs1899663 polymorphism and disease-free survival in kidney cancer patients - VolkogonА.; Harbuzova, V.; Ataman, A.; Harbuzova, Ye.; Kolnoguz, A. (Ukrainian Journal of Nephrology and Dialysis, 2020)
The aim of the current study was to investigate the possible association of HOTAIR gene rs1899663 polymorphism with kidney cancer patients survival and clinicopathological characteristics of kidney cancer. Methods. The whole venous blood of 101 patients with clear cell renal cell carcinoma (CCRCC) (42 women and 59 men) was used in the study. Genotyping of rs1899663 HOTAIR gene polymorphic locus was performed by polymerase chain reaction followed by restriction fragment length polymorphism analysis (PCR-RFLP). Statistical analysis was performed using SPSS (version 17.0). The Kaplan-Meier test and the Cox regression were used to test the possible association between rs1899663 polymorphism of long non-coding RNA HOTAIR gene and the age of CCRCC onset. P values ​​< 0.05 were considered as statistically significant. Results. The results of HOTAIR gene rs1899663 polymorphism genotyping showed that the ratio of GG-homozygotes, GT-heterozygotes and TT-homozygotes in CCRCC patients was 39.6%, 52.5%, and 7.9%, respectively. This distribution did not deviate from the expected by Hardy-Weinberg law (P = 0.143). Results of one-way ANOVA showed that rs1899663-locus of HOTAIR gene was not associated with tumor size of CCRCC patients (P > 0.05), was not related to body mass index, erythrocyte sedimentation rate, fasting glucose, hemoglobin, creatinine and leukocyte amount in the blood of CCRCC patients (P > 0.05). In addition, the results of the Kaplan-Meyer test showed that life expectancy until the CCRCC occurrence does not depend on rs1899663 SNP (log-rank P = 0.739). At the same time, the results of Cox regression analysis both before and after adjusting for covariates (sex, body mass index, metastases, smoking habits and alcohol abuse) showed that CCRCC risk development with age does not depend on HOTAIR gene rs1899663 polymorphism (P > 0.05). Conclusions. This is the first report about the possible link between HOTAIR gene polymorphism and survival of kidney cancer patients both in Ukraine and worldwide. The rs1899663 polymorphic site of HOTAIR gene is not associated with the age of CCRCC onset in the Ukrainian population. In addition, the rs1899663 SNP is also not related to tumor size and clinical фтв laboratory data in patients with kidney cancer.